Émile Durkheim: un sociologo del lavoro contemporaneo? - Bianco, Adele (SocietàMutamentoPolitica, 2017)
This paper drafts a Durkheim’s profile as a work sociologist and highlights his relevance. The paper is structured as follows. The first paragraph is devoted to the industrial relations model proposed by Durkheim, based on the professional groups. This point is a well-known issue of the Durkheim’s sociology of work. According to his approach, the professional groups make possible to develop a more cohesive society. The second paragraph is devoted to a comparison between the modernized corporations by Durkheim with the today “Bilateral Corporations”. The latter are, in Italy and in other European countries, the outcome of bargaining process within small companies. The third paragraph is focused on the work quality and the work relationship topic. The Durkheim’s approach related to it seems to be an anticipation of the today labour policies promoted by the international organizations in improving decent work and bettering the working conditions.